KAJIAN POTENSI PERENCANAAN WILAYAH KOTA BINJAI SUMATERA UTARA - Yuanita F.D Sidabutar; Edi Indera (Jurnal Potensi, 2021)
The potential of Binjai City is the border area of Medan City and areas outside Medan City (Aceh, Langkat, Stabad and others). The city of Binjai has 5 sub-districts with 37 villages. Located approximately 25 km from the center of Medan City, Binjai City is a city that has the potential to become a transit city with its boundaries that can reach many areas so that transportation facilities must be developed as much as possible. Objectives 1) Understand information on the potential of the Binjai City area. 2) Knowing the condition of the potential development of Binjai City. 3) Informing the development of the potential of the Binjai City area. Binjai City. The study data on the potential for regional planning of Binjai City has 1) Binjai City has culinary potential 2) Binjai City has transit terminal facilities, 3) Binjai City has tourism places in several villages. The results of this study were carried out using analytical techniques from survey results to the field in the form of analysis of the condition of regional potential, and data from the distribution of questionnaires in the form of percentage statistical analysis results. And also obtained the concept of thinking for how to increase the economic value of Binjai City.